(untitled) (Physical Education, Health and Social Sciences, 2025)
Fungal diseases cause huge losses in terms of yield and quality of wheat grains which ultimately affect food security of a country. Previously, a number of techniques including agrochemical, breeding and chromosome hybridization adopted were time consuming as well as failed in host resistance ability. In wheat, a recalcitrant crop, genetic improvement remained behind than other cereals. Molecular mapping, marker assisted selection (MAS), functional genomics and cloning have enabled the breeders to develop reliable resistance against fungal diseases. First transformation in wheat was done in 90s and afterwards several antifungal genes have been transformed as an alternative for fungicides. Among the fungal diseases, Fusarium head blight (FHB), producing mycotoxins, not only affects plant but human as well as mongastric animals. FHB antifungal genes such as Fhb1, NPR1 (Arabidopsis thaliana nonexpressor of pathogenesis-related gene), FsTRI101 (Trichothecene 3-O-acetyltransferase from Fusarium sporotrichioides), transcription factors TaWRKY45 (WRKY from Triticum aetivum) and HvUGT1324 (UDP-glucosyltransferase from Hordeum vulgare) have been introduced either to reduce toxin severity or confer fungal resistance. HIGS (host induced gene silencing) has also recently contributed in imparting disease resistance against FHB. There is still much more to be discovered that will further confer more reliable resistance against FHB in future.